Giving Dracula the Keys to the Blood Bank? Interrogating the Fifth Crown Casino Licensing Regulatory Review - Hancock , Linda (Journal of Law and Governance, 2013)
Drawing on narrative analysis, this paper analyses the 2013 Fifth Regulatory Review of the license of an Australian casino as a case study focused on the framing and articulation of ‘responsible gambling’ (RG) in the Review. Part 1 sets out the policy and regulatory context for the licensing review of Melbourne’s Crown Casino. Part 2 overviews the structure/content of the Review; the key messages of the Reviewers’ narrative and its main recommendations. In reflecting on the Review in Part 3, analysis focuses on the investigation and recommendations regarding Responsible Gambling, which has gained recent policy priority. The analysis interrogates the Review’s findings, narratives, processes and evidentiary base in relation to how it presents and assesses casino performance on RG. In doing so, it focuses on the Victorian Commission for Gambling and Liquor Regulation’s Review’s framing of RG; sources of evidence drawn on by the Review; an assessment of the casino’s loyalty club feature ‘Play Safe’, as an RG measure; the Review’s assessment of casino performance on RG and its Code of Conduct in particular; and the Review’s framing of RG recommendations. It concludes with reflections on governance issues raised by the Review, the need for more focus on the neglected area of regulatory licensing and enforcement (OECD, 2011; 2012; OECD & European Commission, 2009) and the need for independent regulatory reviews that address conflicts of interest on the part of both Government and the Regulator.